ANALISIS PENERAPAN METODE BALANCE SCORECARD SEBAGAI PENGUKURAN KINERJA PADA PUSKESMAS MARO SEBO ILIR BATANGHARI - Intan Syahrina; Yudi; Yetti, Susfa (Jurusan Akuntansi FEB Universitas Jambi, 2023)
This study aims to determain the performance analysis at the Maro Sebo Ilir Healt Center, Batanghari District, using the Balance Scorecard method. In analyzing the data researchers used qualitive methods. This analysis is based on interviews and by looking at existing data at the puskesmas, both financial and non-financial data. The sample in this study, namely performance of the financial perspective, the performance of the customer perspective, the performance of the internal business process perspective, and the performance of the growth and learning perspective. The result of the study using the Balance Scorecarad method at the Maro Sebo Ilir Healt Center show at the financial perspective which has an everage results is more effective than the results of the four research variables. The results showed than the Balance Scorecard analysis from the UPT Puskesmas Maro Sebo Ilir had Performed poorly, namely 80% was below the standard set at 80% - 100%%. Keyward : Balance Scorecard, Performance Measurement, Performance of the Maro Sebo Ilir Healt Center